Fatal Delftia acidovorans infection in an immunocompetent patient with empyema - Khan, Sadia (Asian Pacific Tropical Medicine Press, 2012)
Delftia acidovorans (earlier known as Comamonas acidovorans) is an aerobic, non-fermentative, Gram negative rod, classified in the Pseudomonas rRNA homology Group III. Reports of isolation of the organism from serious infections like central venous catheter associated bacteremia, corneal ulcers, otitis media exist. The microbiologists can identify this organism based on an orange indole reaction. This reaction demonstrates the organism's ability to produce anthranilic acid from tryptophan on addition of Kovac's reagent; which gives the media its characteristic “pumpkin orange” colour. Here we report the isolation of this organism from the Endotracheal tube aspirate of a 4 year old child. With the increasing use of invasive devices, it has become important to recognize these non fermentative gram negative bacilli as emerging source of infection even in immunocompetent individuals.